The epidemiology and burden of Plasmodium falciparum-related anemia among pregnant women in sub-Saharan Africa. - Guyatt, H; Snow, R (2001)
The paucity of precise information on the burden of malaria among pregnant women has hampered effective lobbying for the inclusion of preventative strategies against malaria in Safe Motherhood Initiatives. This article reviews the evidence on the coincidental risks of malaria and anemia in Africa and attempts to estimate the probable burden of malaria-related severe anemia in this susceptible group. Twenty-six studies on hemoglobin levels in all-parity pregnant women throughout this region could be matched with a malaria parasite ratio in children < 15 yr old (a measure of the intensity of transmission). In areas with no malaria, the mean hemoglobin levels were markedly higher than those found in areas with stable malaria transmission, though changes with increasing intensity of transmission were unclear. Eighteen studies from areas with stable malaria transmission in sub-Saharan Africa suggested that the median prevalence of severe anemia in all-parity pregnant women is approximately 8.2%. Assuming that 26% of these cases are due to malaria, it is suggested that as many as 400,000 pregnant women may have developed severe anemia as a result of infection with malaria in sub-Saharan Africa in 1995.